Scintillation of PSR B1508+55 – the view from a 10 000-km baseline. Issue 4 (19th July 2021) - Marthi, V R; Simard, D; Main, R A; Pen, U-L; van Kerkwijk, M H; Vanderlinde, K; Gupta, Y; Roberts, C; Quine, B M
ABSTRACT: We report on the simultaneous Giant Metrewave Radio Telescope (GMRT) and Algonquin Radio Observatory (ARO) observations at 550–750 MHz of the scintillation of PSR B1508+55, resulting in an ∼10 000-km baseline. This regime of measurement lies between the shorter few 100- to 1000-km baselines of earlier multistation observations and the much longer earth–space baselines. We measure a scintillation cross-correlation coefficient of 0.22, offset from zero time lag due to a ∼45-s traversal time of the scintillation pattern. The scintillation time of 135 s is 3× longer, ruling out isotropic as well as strictly one-dimensional scattering. Hence, the low cross-correlation coefficient is indicative of highly anisotropic but two-dimensional scattering. The common scintillation detected on the baseline is confined to low delays of ≲1μs, suggesting that this correlation may not be associated with the parabolic scintillation arc detected at the GMRT. Detection of pulsed echoes and their direct imaging with the Low-Frequency Array (LOFAR) by a different group enable them to measure a distance of 125 pc to the screen causing these echoes. These previous measurements, alongside our observations, lead us to propose that there are at least two scattering screens: the closer 125-pc screen causing the scintillation arc detected at GMRT, and a screen further beyond causing the scintillation detected on the GMRT-ARO baseline. We advance the hypothesis that the 125-pc screen partially resolves the speckle images on the screen beyond leading to loss of coherence in the scintillation dynamic spectrum to explain the low cross-correlation coefficient.